Consumo de amido e proteína, excreção de oxalato e características da urina de gatos alimentados com ração seca - Pedreira, Raquel Silveira [UNESP] (2015)
Cats are carnivores and have high amino acids requirements. The use of carbohydrates by these animals has been evaluated; however, there are some information that is not well understood. The objective of this study was to evaluate the effect of consumption of diets with different relations between starch and protein on the formation and excretion of oxalate, and the relative supersaturation index of calcium oxalate in urine (SSR OxCa). Four diets were extruded with different starch (CHO) and protein (CP) ratios: diet 47 with 47% of CHO and 25% of CP; diet 32 with 31.9% of CHO and 38% of CP; diet 19 with 19.2% of CHO and 52% of CP; and diet 8 with 8.3% of CHO and 62% of CP (dry matter basis). The experiment was organized in 4 blocks of 18 days; there were 4 diets and 8 cats in each block, resulting in eight animals per diet. Animals were kept in metabolic cages during 10 days for diet adaptation followed by 7 days of total urine and feces collection. Urine was collected in bottles with 1 ml of H2SO4 (1N) in the first two days of the collection period and the last five days in bottles with 100 mg of thymol. Volume, density and pH of urine were measured each 24 hours during the whole experiment. Urine harvested with thymol were homogenized and analyzed for calcium, phosphorus, chlorine, sulfur, magnesium, sodium, potassium, citrate, oxalate, uric acid and creatinine. In the acidic urine were determined nitrogen and gross energy. Blood samples were taken at 18th day of the experiment and evaluated for oxalate and creatinine. Food and feces were evaluated for dry matter, ash, starch, crude fiber and gross energy. Based on the results SSR OxCa and fractional excretion of oxalate were calculated. Data were submitted to analysis of variance and when significant differences were detected in the F test, multiple comparisons were performed using polynomial contrasts (P <0.05). Starch inclusion up to 47% did not restrict the diet consumption by ...